Characteristic scales of two‐dimensional turbulence in polymer solutions. Issue 5 (24th January 2014) - Hidema, Ruri; Suzuki, Hiroshi; Hisamatsu, Shion; Komoda, Yoshiyuki
<x xml:space="preserve">Abstract</x> An experimental study has been performed to investigate the relationship between the extensional viscosity of polymers and the turbulent drag reduction. Self‐standing flowing soap film was used to generate two‐dimensional (2‐D) turbulent flow to eliminate shear stress. Two types of polymers having different flexibilities were added to the 2‐D turbulence. The effects of these polymers were visualized by the interference pattern of flowing soap films. The vortex deformation by adding polymers was analyzed by Fourier transformation and wavelet transformation. The scaling exponents of the power spectrum of interference patterns indicate that the mechanism of turbulence laminarization due to the extensional viscosity is anisotropic. A wavelet analysis reveals the high and low fluctuations of the polymer‐added flow. Results from wavelet analysis indicate disappearing of original vortices, and appearing of new structures in low frequency in 2‐D flow. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1854–1862, 2014